Lembaga Pendidikan Islam Bali di Era Revolusi Industri 4.0 - Fawaid, Mohammad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
The presence of the Industrial Revolution 4.0, it automatically affected the process of scientific development in Islamic education. The development was felt in aspects of its objectives, teaching methodology, and learning media, and the competency standards of graduates who have soft skills and hard skills. Especially after seeing the development of new student enrollments in each Islamic educational institution from year to year experienced a surge so drastically that many Islamic Education institutions in Bali especially in Denpasar and Badung regency had to reject new prospective students because of insufficient class location. This indication is a phenomenon that competition in science and technology at the level of primary and secondary education institutions is increasingly opening up space for education managers to complete facilities and infrastructure that support the progress of students based on Islamic ideology and teachings, because Islamic Education institutions in Bali are at the majority Hindu environment. Islamic Education Institutions which have always been considered less good, I have forbidden for some parents to become